The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.nanolett.0c01836
|View full text |Cite
|
Sign up to set email alerts
|

Low-Voltage Domain-Wall LiNbO3 Memristors

Abstract: Application of conducting ferroelectric domain walls (DW) as functional elements may facilitate development of conceptually new resistive switching devices. In a conventional approach, several orders of magnitude change in resistance can be achieved by controlling the DWs density using super-coercive voltage. However, a deleterious characteristic of this approach is high-energy cost of polarization reversal due to high leakage current. Here, we demonstrate a new approach based on tuning the conductivity of DWs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…[13][14][15][16][17] However, till now, only HZO-based gate stack 2D NC-FETs can obtain ultralow SS (<10 mV dec −1 ) and quasi-free hysteresis simultaneously. [14] As a ferroelectric materials system with excellent ferroelectric and electro-optic properties, single crystal LiNbO 3 (LNO) has attracted huge attention, [25][26][27][28] which shows the largest spontaneous polarization (50-80 µC cm −2 ) and possesses unique ferroelectric domains direction with only the +c and the −c. Recently, owing to full-fledged preparation of high-quality single crystal LNO thin film by ion-implanted method, the CMOS-compatible LNO integrated system is realized and becomes a promising candidate for future electronic and optical integrated chips.…”
Section: Doi: 101002/adma202005353mentioning
confidence: 99%
“…[13][14][15][16][17] However, till now, only HZO-based gate stack 2D NC-FETs can obtain ultralow SS (<10 mV dec −1 ) and quasi-free hysteresis simultaneously. [14] As a ferroelectric materials system with excellent ferroelectric and electro-optic properties, single crystal LiNbO 3 (LNO) has attracted huge attention, [25][26][27][28] which shows the largest spontaneous polarization (50-80 µC cm −2 ) and possesses unique ferroelectric domains direction with only the +c and the −c. Recently, owing to full-fledged preparation of high-quality single crystal LNO thin film by ion-implanted method, the CMOS-compatible LNO integrated system is realized and becomes a promising candidate for future electronic and optical integrated chips.…”
Section: Doi: 101002/adma202005353mentioning
confidence: 99%
“…The possibilities afforded by controllable "now-you-see-it-now you-don't" mercurial conducting domain wall conduits for new kinds of devices were noted in Siedel et al's seminal work [6], where a proof-of-concept memristor was even explicitly demonstrated: conduction states were varied by writing different numbers of domain wall channels between source and drain electrodes using a conducting AFM tip. More operationally pragmatic domain wall memristors [33][34][35][36], transistors [37] and binary memory bits [38,39] have since been developed and their potential applications are growing (in neuromorphic circuitry, for example).…”
Section: Potential For Applicationsmentioning
confidence: 99%
“…Additionally, through electrical control of the wall length, [ 24 ] wall charge state/conformation, [ 136,137 ] and density, [ 138 ] multi‐level states or the ‘memristor device’ promising much higher storage densities than what can be achieved with just binary logic were demonstrated. In fact, by varying the magnitude of applied electrical pulses, the domain wall density in a two‐terminal capacitor was tuned to achieve ≈100 different states (within two orders of magnitude change in resistance).…”
Section: State‐of‐the‐art Knowledgementioning
confidence: 99%